Kinematics of a screw linkage - Jing-Shan Zhao (Springer, 2021)
Article highlights 1. The angular and linear velocities of each link of a series linkage are expressed by the twists of its predecessors. 2. Loop equation of velocity provides a convenient way to gain both forward and inverse kinematics for a closed linkage. 3. Forward and inverse displacement and acceleration of the linkage are calculated by integral and differential methods, numerically or analytically.